INFORMATION ACCESS AND LEARNING MEDIA EFFECTS ON ISLAMIC FINANCIAL LITERACY AMONG MADRASAH STUDENTS - Rahman, Rahman; Syahriyah Semaun; Damirah; St Aminah; Muzdalifah Muhammadun (Jurnal Al-Kharaj: Studi Ekonomi Syariah, Muamalah, dan Hukum Ekonomi, 2026)
This study examines how access to information and learning media impact students' Islamic financial literacy in the digital era. This study uses a quantitative associative approach to analyze the influence of access to information and learning media on students' Islamic financial literacy in the digital era. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics, Pearson correlation, and multiple linear regression with t-tests and F-tests. The findings indicate that access to information has a positive and significant effect on Islamic financial literacy. Learning media also exhibits a positive and significant effect, with a stronger effect than access to information. Together, both variables significantly influence students' Islamic financial literacy, highlighting the importance of an integrated learning approach. This study concludes that learning media and access to information significantly influence Islamic financial literacy, with learning media playing a more dominant role. These results suggest that policymakers and educational institutions should strengthen Islamic financial education through innovative and values-based learning media. Future studies are encouraged to incorporate additional factors to enrich our understanding of the development of Islamic financial literacy.